Non-vitamin K antagonist oral anticoagulants (NOACs) attenuate valvular calcification in patients with severe aortic stenosis. (3rd October 2022) - Kopytek, M; Tarasiuk, J; Wronski, S; Undas, A; Natorska, J
Abstract: Background: In vitro studies has demonstrated that non-vitamin K antagonist oral anticoagulants (NOACs) down-regulated the expression of proteins responsible for valve calcification and inflammation in valve interstitial cells (VICs) cultures. Aims: Our goal was to evaluate whether long-term anticoagulation with NOACs, including dabigatran (thrombin inhibitor), rivaroxaban and apixaban (FXa inhibitors) can impair the valvular calcification and inflammation in patients with severe AS. Methods: We enrolled 38 patients with severe AS aged 70±5.9 years (mean gradient - PGmean: 50mmHg, max gradient - PGmax: 80mmHg), including 18 individuals with AS and concomitant atrial fibrillation taking NOACs for at least 3 years (51±10 months) (AS-NOACs group). Stenotic aortic valves were obtained during valve replacement surgery. Valvular calcification was estimated ex vivo using micro-computed tomography (micro-CT). Total volume of each calcification (bone volume - BV), the distribution of clods sizes of calcification parts (trabecular thickness -Tbth) and the volume of the hardest / most calcified part (hard CT) of each valve were assessed. Valvular expression of bone morphogenetic protein 2 (BMP-2) and NFκB was evaluated by immunostaining. The fluorescence intensity (FI) was computed as the ratio (%) of positively and negatively stained areas. Results: AS patients did not differ from AS-NOACs participants with regard to demographic or risk factors. Micro-CT analysis showed 65.5% lower BV in AS-NOACs valves compared to patients not taking NOACs (87±47 mm 3 vs. 252±146 mm 3, p=0.0017). Of note, in AS-NOACs patients Tbth showed strong association with transvalvular pressure gradients (PGmean: r=0.76, p=0.033; PGmax: r=0.77, p=0.01), as clinical measures of the AS severity. The duration of anticoagulation was associated with the lower Tbth (from 0.35 mm for 60 months to 0.51 mm for 36 months, p<0.01), which suggests that long NOACs treatment changed the pattern of valvular calcification, leading to formation of calcium deposits with reduced volume. Moreover, in AS-NOACs patients BV correlated with hard CT (r=−0.69, p=0.027), suggesting that the lesions increase their volume but do not ossify. Valvular expression of BMP-2 and NFκB was 44% and 33% decreased in AS-NOACs patients, compared to those without such treatment and the expression of both proteins was positively associated (r=0.34, p=0.001). Moreover, in AS-NOACs patients the expression of BMP-2 and NFκB was observed mainly in the fibrosa layer of the leaflets, but not in the deeper layers of tissue, as in AS patients without NOACs treatment. Conclusions: NOACs can inhibit the increase of valvular calcium volume and its ossification via suppressed NFkB expression. Our study may suggest that long-term anticoagulation with NOACs could slow down the rate of AS progression, at least in patients with an indication for anticoagulant therapy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Polish National Science Centre